Outcomes from the Introduction of a Combined Urology Outpatient Clinic - Clíodhna Browne; Catherine M. Dowling; Patrick O’Malley; Nadeem Nusrat; Kilian Walsh; Syed Jaffry; Eamonn Rogers; Garrett C. Durkan; Frank T. D’Arcy (Advances in Urology)
Background. A combined urology clinic staffed by four consultants and four non‐consultant hospital doctors (NCHDs) was introduced in our institution in October 2015. This clinic is supported by a pre‐clinic radiology meeting and a synchronous urology clinical nurse specialist (CNS) clinic with protected uroflow/trial of void slots. Herein, we report on the outcomes of this clinic in comparison with the standard format of urology outpatient review. Methods. We carried out a retrospective review of clinic attendances from May to July 2016. We recorded the number of new and return attendances, which team members had reviewed the patient and patient outcomes. We also calculated the waiting times for new patients to be reviewed in the outpatient clinic. Results. The combined urology clinic reviewed an average of 12 new and 46 return patients per clinic. The standard urology clinic reviewed an average of 8 new and 23 return patients per clinic. 54% of patients were seen by a consultant in the combined urology clinic, and 20% of patients were seen by a consultant in the standard urology clinic. The rate of patient discharge for new patients was 14.8% in the combined clinic compared to 5.9% in the standard clinic. Overall patient outcomes are outlined in the table. The waiting time for review of new patients in the combined clinic was reduced by 39% from 144 days to 89 days over a one-year period. Conclusions. The introduction of a combined urology outpatient clinic with the support of pre‐clinic radiology meeting and synchronous urology CNS clinic facilitates patient discharge.